Pengaruh Ekonomi Orang Tua Siswa terhadap Peningkatan Prestasi Belajar Siswa Kelas VII MTs Raudlatul Wathoni Taman Sari: The Influence of Parents' Economic Status on Improving Student Learning Achievement in Class VII MTs Raudlatul Wathoni Taman Sari - Ahmad Salman Alparizi (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
Children's education is a very important thing in efforts to build and develop children's potential in the future, so this education is very important for the progress of the nation, society, family, and parents. The purpose of this study was to determine the influence of parents' economic status on improving student achievement at MTs Raudlatul Wathoni Taman Sari. The method used is the ex post facto research method. The population of the study was 25 students of class VII MTs Raudlatul Wathoni Taman Sari. The sample of this study was the entire population. The instruments used to collect data were questionnaires and documentation. To analyze the data, the t-test was used. The results of this study concluded that the economic situation of parents did not have a significant effect on student achievement at class VII MTs Raudlatul Wathoni Taman Sari. Based on the hypothesis test conducted, the calculated value was obtained = 1.27 while the t table at a 5% error level was 1.714, so it was concluded that the alternative hypothesis (Ha) was not accepted.